Проблемні питання обліку списаної кредиторської заборгованості - Голуб, Наталя Олександрівна; Голуб, Наталья Александровна; Holub, Natalia; Вольська, А. О. (My University, 2019)
UK: У статті розкрито сутність кредиторської заборгованості. Проаналізовано роль безнадійної та сумнівної заборгованості в сучасних умовах господарювання. Визначено причини виникнення безнадійної кредиторської заборгованості. Розглянуто основні напрями списання безнадійної кредиторської заборгованості. Розкрито особливості податкового та бухгалтерського обліку списаної кредиторської заборгованості. Встановлено проблемні питання податкового та бухгалтерського законодавства безнадійної та сумнівної кредиторської заборгованості. Розглянуто податкові наслідки з податку на додану вартість у разі списання кредиторської заборгованості у зв’язку із закінченням строку позовної давності за авансами, поставка товару за якими не відбулась. Визначено шляхи врегулювання списаної заборгованості в обліку. RU: В статье раскрыта сущность кредиторской задолженности. Проанализирована роль безнадежной и сомнительной задолженности в современных условиях хозяйствования. Определены причины возникновения безнадежной кредиторской задолженности. Рассмотрены основные направления списания безнадежной кредиторской задолженности. Раскрыты особенности налогового и бухгалтерского учета списанной кредиторской задолженности. Установлены проблемные вопросы налогового и бухгалтерского законодательства безнадежной и сомнительной кредиторской задолженности. Рассмотрены налоговые последствия по налогу на добавленную стоимость при списании кредиторской задолженности в связи с истечением срока исковой давности по авансам, поставка товаров по которым не состоялась. Определены пути урегулирования списанной задолженности в учете. EN: The essence of debt is revealed in the article. There are situations when the company does not fulfill its obligations to its counterparty and becomes a debtor. First of all, we need to check the reliability of information on the types and terms of payables. To do this, use direct confirmation of contractors, study contracts and contracts, personal interviews with employees who have information about debts and obligations of the enterprise. Commitment is the debt of an enterprise that arose as a result of past events and the settlement of which is expected to lead to a reduction in the resources of an enterprise that embody economic benefits. Bad receivables are current receivables, about which there is confidence in its non-return by the debtor or on which the expiry of the limitation period. The role of bad and doubtful debts in the current economic conditions is analyzed. To offset as accounts payable, such debt should correspond to bad debts. It is important when payables become hopeless for accounting and tax accounting. In the tax context, its definition of bad debt relates to value added tax. For a profit tax, everything depends on accounting. Namely, when income is recognized for bad payables. If at the balance sheet date the previously recognized liability is not repayable, its amount is included in the income of the reporting period. The reasons for the occurrence of bad payables are determined. The main directions of write-off of bad payables are considered. The peculiarities of tax and accounting of the written off accounts payable are revealed. Problematic issues of tax and accounting legislation of doubtful and doubtful accounts payable are established. The tax consequences of the value added tax in the event of write-off of accounts payable due to the expiration of the limitation period for advances are considered, delivery of goods for which did not occur. Limitation period is the time when a person may apply to a court for the protection of his civil right or interest. Possibility of adjusting the received advance of the amount of tax liability on the basis of the calculation of the adjustment to the tax invoice is revealed. In this case, the limitation period is more than 1095 calendar days. In tax legislation, this problem concerns only the supplier. The settlement ways of written off debts in the account are determined.
Проблемные вопросы учета списанной кредиторской задолженности
Problematic issues of accounting of write-off accounts payable
Keywords: облік; позовна давність; зобов’язання; кредиторська заборгованість; кредитори; списана кредиторська заборгованість; поточна заборгованість; податкове зобов’язання; податковий кредит; розрахунок коригування; податкова накладна; учет; исковая давность; обязательства; кредиторская задолженность; кредиторы; списанная кредиторская задолженность; текущая задолженность; налоговое обязательство; налоговый кредит; расчет корректировки; налоговая накладная; accounting; limitation; liabilities; accounts payable; creditors; write-off accounts payable; current payables; tax liability; tax credit; adjustment of accounts; tax invoice